2015
DOI: 10.1039/c5cp00145e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of halogen substitutions on rates of charge tunneling across SAM-based large-area junctions

Abstract: This paper examines the ability of structural modifications using halogen atoms (F, Cl, Br, and I) to influence tunneling rates across self-assembled monolayer (SAM)-based junctions having the structure Ag(TS)/S(CH2)n(p-C6H4X)//Ga2O3/EGaIn, where S(CH2)n(p-C6H4X) is a SAM of benzenethiol (n = 0) or benzyl mercaptan (n = 1) terminated in a hydrogen (X = H) or a halogen (X = F, Cl, Br, or I) at the para-position. The measured tunneling current densities (J(V); A cm(-2)) indicate that replacing a terminal hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 29 publications
(39 reference statements)
4
45
2
5
Order By: Relevance
“…These authors also showed that ε r of conjugated SAMs is less sensitive to the presence of highly polarizable atoms than non‐conjugated SAMs, which explains why we observed a factor of 4 increase of ε r . This notion also explains why Yoon et al only observed marginal effects in the tunneling rates in EGaIn junctions of the form Ag TS –S(CH 2 ) n ( p ‐C 6 H 5 X)//GaO x /EGaIn with n = 0 or 1 and X = H, F, Cl, Br, and I (these authors did not measure ε r ) . In addition, these short and conjugated SAMs hybridize strongly with the bottom‐electrode masking molecular effects …”
Section: The Properties Of the Samsmentioning
confidence: 98%
“…These authors also showed that ε r of conjugated SAMs is less sensitive to the presence of highly polarizable atoms than non‐conjugated SAMs, which explains why we observed a factor of 4 increase of ε r . This notion also explains why Yoon et al only observed marginal effects in the tunneling rates in EGaIn junctions of the form Ag TS –S(CH 2 ) n ( p ‐C 6 H 5 X)//GaO x /EGaIn with n = 0 or 1 and X = H, F, Cl, Br, and I (these authors did not measure ε r ) . In addition, these short and conjugated SAMs hybridize strongly with the bottom‐electrode masking molecular effects …”
Section: The Properties Of the Samsmentioning
confidence: 98%
“…[41] In contrast to these results, for junctions with a conjugated backbone, Au-S(Ph) m X//GaO x /EGaIn (Ph = phenyl, X = F, Cl, Br, or I, m = 1 or 2), the identity of X did not change the charge transport characteristics of the junctions. [42,170] Figure 15a shows that the J(V) curves are essentially independent of X, except for X = H for which the currents are a factor of 10 larger than for the halogenated SAMs. [42] The value of R C obtained from IS is independent of X, and ε r only marginally increases from 2.3 to 3.2 in sharp contrast to the fourfold increase of ε r for S(CH 2 ) 11 X SAMs (Figure 14d).…”
Section: Collective Electrostatic Effectsmentioning
confidence: 99%
“…Such an influence, in the case of the terminal halogen atom, was reported for several aromatic SAMs, based on the static conductance data. 34,35,37 Whereas a terminal substitution is regretfully not possible within the molecular design suitable for RAES-CHC experiments, the side substitutions, performed for the benzonitrile-based SAMs (Figure 10) do not affect the ET dynamics noticeably, if one compares the average values for τ ET (π 1 *) and τ ET (π 3 *) with those for the nonsubstituted NC-PT SAM (Figure 4a), viz. 9 ± 3 fs and 31.5 ± 6 fs, respectively.…”
Section: ■ Direct Coupling To the Substratementioning
confidence: 99%
“…Apart from the negligible effect of the molecular dipole, the spectra of the benzonitrile-based SAMs are relevant in context of possible influence of halogen substitution, and fluorine in particular, on the electric transport properties of aromatic monolayers. Such an influence, in the case of the terminal halogen atom, was reported for several aromatic SAMs, based on the static conductance data. ,, Whereas a terminal substitution is regretfully not possible within the molecular design suitable for RAES-CHC experiments, the side substitutions, performed for the benzonitrile-based SAMs (Figure ) do not affect the ET dynamics noticeably, if one compares the average values for τ ET (π 1 *) and τ ET (π 3 *) with those for the nonsubstituted NC-PT SAM (Figure a), viz. 9 ± 3 fs and 31.5 ± 6 fs, respectively …”
Section: Effect Of Molecular Dipole and Substitutionmentioning
confidence: 99%